2022
DOI: 10.1177/10634266221130049
|View full text |Cite
|
Sign up to set email alerts
|

Professional Development: Improving Teachers’ Knowledge and Self-Efficacy Related to Emotional and Behavioral Disorders

Abstract: Teachers should possess adequate knowledge of emotional and behavioral disorders (EBDs) to effectively meet the unique needs of students with EBDs. This study explored the implementation and outcomes of a professional development training program on EBDs. In addition, the study examined outcomes concerning the knowledge of in-service teachers about EBDs and their self-efficacy in working with students with EBDs. This study recruited 81 general education teachers from two elementary schools, assigned under the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 87 publications
(90 reference statements)
1
1
0
Order By: Relevance
“…The findings are consistent with Evans [17] and Ref. [40], indicating that exposure to sustainability pedagogies improves teachers' self-efficacy, and the same may be true for the relationship between teachers' self-efficacy and readiness. A teacher's belief in their capacity to execute ESD teaching tasks efficiently may also inform their level of preparedness to execute said teaching activities.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The findings are consistent with Evans [17] and Ref. [40], indicating that exposure to sustainability pedagogies improves teachers' self-efficacy, and the same may be true for the relationship between teachers' self-efficacy and readiness. A teacher's belief in their capacity to execute ESD teaching tasks efficiently may also inform their level of preparedness to execute said teaching activities.…”
Section: Discussionsupporting
confidence: 83%
“…Ref. [40] found that professional development training programs significantly increase teachers' knowledge and self-efficacy. Similarly, Ref.…”
Section: Teachers' Sustainability Knowledge and Self-efficacy In Esdmentioning
confidence: 99%